2015
DOI: 10.1016/j.jhep.2015.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Hyperammonemia in ICU patients: A frequent finding associated with high mortality

Abstract: Please cite this article as: Prado, F.A., Delfino, V.D.A., Grion, C.M.C., de Oliveira, J.A., Hyperammonemia in ICU Patients: A Frequent Finding Associated with High Mortality, Journal of Hepatology (2015), doi: http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 12 publications
1
26
0
Order By: Relevance
“…In this study, we found the incidence of hyperammonemia in critical care patients without liver disease to be 42.2%. A recent prospective observational study with one hundred patients found, after excluding those patients with acute or chronic liver disease, hyperammonemia was observed in 40% of patients on their first day in the ICU and 60% by their third day in the ICU (5) A retrospective observational cohort study conducted on critically ill patients admitted to six ICUs found the lowest incidence of NHH in the literature at 8.6%, (4) while the highest recorded incidence was 73% (5) In previous studies, the largest sample size of non-hepatic hyperammonemia patients was still relatively small at 167 patients, (4) while the smallest sample size was 78 patients (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we found the incidence of hyperammonemia in critical care patients without liver disease to be 42.2%. A recent prospective observational study with one hundred patients found, after excluding those patients with acute or chronic liver disease, hyperammonemia was observed in 40% of patients on their first day in the ICU and 60% by their third day in the ICU (5) A retrospective observational cohort study conducted on critically ill patients admitted to six ICUs found the lowest incidence of NHH in the literature at 8.6%, (4) while the highest recorded incidence was 73% (5) In previous studies, the largest sample size of non-hepatic hyperammonemia patients was still relatively small at 167 patients, (4) while the smallest sample size was 78 patients (18).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated blood ammonia levels without a history of liver disease is defined as non-hepatic hyperammonemia (NHH). NHH can be quite common in critically ill patients (up to 73% in a recent study) (5). NHH can occur in patients with a variety of serious conditions, such as intracranial hypertension (6) or congestive heart failure, malnutrition, infectious enterocolitis, or lung transplantation (7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Non-cirrhotic hyperammonaemic encephalopathy (NCHAE) is less common; however, it is increasingly being recognised as a cause of encephalopathy. Hyperammonaemia in patients in the intensive care unit is associated with high mortality, and hyperammonaemic encephalopathy can progress from confusion to coma with cerebral oedema, brain stem herniation and death 2. We present a case highlighting that hyperammonaemia in NCHAE may be multifactorial in origin.…”
Section: Introductionmentioning
confidence: 91%
“…Most patients with non-hepatic hyperammonemia present with confusion and coma [23,24]. Nonhepatic hyperammonemia in intensive care unit (ICU) patients has especially high morbidity and mortality [25,26]. There are several reviews and case reports on hyperammonemia in non-hepatic disease and ICU patients, but large observational studies on non-hepatic hyperammonemia are limited [24,26].…”
Section: Introductionmentioning
confidence: 99%
“…Nonhepatic hyperammonemia in intensive care unit (ICU) patients has especially high morbidity and mortality [25,26]. There are several reviews and case reports on hyperammonemia in non-hepatic disease and ICU patients, but large observational studies on non-hepatic hyperammonemia are limited [24,26]. Fabrizio et al reported that ammonia levels affect the mortality rates of ICU patients with non-hepatic disease and were correlated with mortality by univariate analysis using the chi-square test in 100 patients with nonhyperammonemia [26].…”
Section: Introductionmentioning
confidence: 99%